2010
DOI: 10.1038/nphys1500
|View full text |Cite
|
Sign up to set email alerts
|

A hitherto unrecognized source of low-energy electrons in water

Abstract: Because ICD is expected to take place universally in weakly bound aggregates containing light atoms between carbon and neon in the periodic table 2,3 , these results could have implications for our understanding of ionization damage in living tissues. NPHYS-2009-06-00979a 2 Electronic vacancy states can be produced in matter by ionizing radiation, such as X-ray photons or fast charged particles. When a state with a high electronic excitation energy has been produced by impact of such particles, electron cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
234
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(243 citation statements)
references
References 30 publications
8
234
0
1
Order By: Relevance
“…[12][13][14] One such relaxation process is Intermolecular Coulombic Decay (ICD), initially observed upon innervalence ionization of van der Waals-bonded clusters, 12,[15][16][17] and later also (hydrogen bonded) water clusters. 18 In the ICD process, the energy provided by an outer valence electron upon filling the vacancy is used to expel a second electron from an atom or molecule neighboring the initially ionized site. Throughout the process the two units (two water molecules in our case) can be considered as being electronically distinct; see scheme Figure 1c.…”
Section: Identifying the Initial Products Of The Interaction Of High-mentioning
confidence: 99%
“…[12][13][14] One such relaxation process is Intermolecular Coulombic Decay (ICD), initially observed upon innervalence ionization of van der Waals-bonded clusters, 12,[15][16][17] and later also (hydrogen bonded) water clusters. 18 In the ICD process, the energy provided by an outer valence electron upon filling the vacancy is used to expel a second electron from an atom or molecule neighboring the initially ionized site. Throughout the process the two units (two water molecules in our case) can be considered as being electronically distinct; see scheme Figure 1c.…”
Section: Identifying the Initial Products Of The Interaction Of High-mentioning
confidence: 99%
“…Recent experiments even suggest that ICD electrons contribute up to about 50% of the single-strand breaks (SSB) in DNA [13]. Moreover, these electrons possess energies at which much harder to repair double-strand breaks (DSB) occur [10,14] and the energetic cations produced in Coulomb explosions may additionally damage the DNA.…”
mentioning
confidence: 99%
“…Atomic and molecular phases comprise mainly localized electronic orbitals, and the decay rate is consequently quite small for processes involving electron emission from any atomic site other than that originally excited. In such systems, this type of ''off-site'' emission has been labeled as ICD, inter-Coulombic (atomic or molecular) decay [3].Although ICD has been studied primarily in the context of valence excitations [3][4][5], recent experiments have shown that core-excited systems may also decay in this fashion, as shown schematically in Fig. 1 [6].…”
mentioning
confidence: 99%
“…Although ICD has been studied primarily in the context of valence excitations [3][4][5], recent experiments have shown that core-excited systems may also decay in this fashion, as shown schematically in Fig. 1 [6].…”
mentioning
confidence: 99%